2021
DOI: 10.3389/fonc.2021.722833
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of CD133 in Predicting the Relapse and Recurrence Pattern of High-Grade Gliomas on MRI: A Meta-Analysis

Abstract: BackgroundCancer stem cells have been implicated in tumor relapse, tumor invasion, and cancer therapy resistance in high-grade gliomas; thus, characterizing cancer stem cell-related markers can help determine the prognosis of affected patients. Preclinical studies have reported that CD133 is implicated in tumor recurrence and cancer therapy resistance in high-grade gliomas; however, clinical studies have reported inconclusive results regarding its prognostic value in patients with high-grade gliomas.MethodsWe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Glioma-initiating cells (GICs) showing a glioma stem cell (GSC) phenotype [ 22 , 23 ] colonize tumor areas with elevated hypoxia and “palisading necrosis” [ 24 , 25 ]. Residual infiltrating GICs result in less sensitivity to therapies and consequently GBM recurrence [ 26 , 27 ]. Moreover, resident nontumor cells, including infiltrating lymphocytes and glioma-associated microglia/macrophages constituting the tumor stroma [ 28 , 29 ], are responsible, in part, for the altered malignancy of GBM, as this cell population supports angiogenesis, growth, and invasiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Glioma-initiating cells (GICs) showing a glioma stem cell (GSC) phenotype [ 22 , 23 ] colonize tumor areas with elevated hypoxia and “palisading necrosis” [ 24 , 25 ]. Residual infiltrating GICs result in less sensitivity to therapies and consequently GBM recurrence [ 26 , 27 ]. Moreover, resident nontumor cells, including infiltrating lymphocytes and glioma-associated microglia/macrophages constituting the tumor stroma [ 28 , 29 ], are responsible, in part, for the altered malignancy of GBM, as this cell population supports angiogenesis, growth, and invasiveness.…”
Section: Introductionmentioning
confidence: 99%
“…We also detected differences in the alternative splicing of prominin 1 mRNA ( Prom1 ) (also known as CD133) and chose to follow up on Prom1 as it is associated with glioma recurrence and cancer therapy resistance (Abdoli Shadbad et al, 2021). We found that this gene undergoes three alternative splicing events that are differentially present in the culture configurations: one in the extracellular domain (EC), and two in the intracellular region (IC1 and IC2) (Figure S5b,c).…”
Section: Resultsmentioning
confidence: 99%
“…45 With a 10% cut-off, CD133 protein overexpression is associated with inferior PFS in patients with glioblastoma. 46…”
Section: Prognostication Factors-biomarkersmentioning
confidence: 99%